CTD data acquired at the OBSEA seafloor observatory from 2013 to 2014 - Enoc Martinez Padro; Marc Nogueras Cervera; Daniel Mihai Toma; Matias Carandell Widmer; Ivan Masmitjà Rusiñol; David Sarrià Gandul; Albert Garcia-Benadí; Marco Francescangeli; Javier Cadena Muñoz; Ikram Bghiel; Carola Artero Delgado; Neus Vidal; et al. (PANGAEA, 2022)
Data from two CTD sensors (SBE37 and SBE16) deployed at OBSEA seafloor observatory from 2013 to 2014. OBSEA station is located 4km off-the-coast of Vilanova i la Geltrú (Catalonia, Spain) at a depth of 20 meters. Measured variables are sea water temperature, conductivity, pressure, salinity and sound velocity. Data from the CTD sensors has been acquired every 10 seconds, then a quality control procedure has been applied following QARTOD guidelines. Afterwards the quality controlled data has been averaged in periods of 30 minutes (discarding data flagged as bad data). Every data point has an associated a quality control flag and standard deviation value. The quality control flag values are 1: good data, 2: not applied, 3: suspicious data, 4: bad data, 9: missing data. The standard deviation provides a measure of the variability of the data within the 30min time window used in the average.